Sistem Pendukung Keputusan Penentuan Alokasi Dana Desa dengan Metode Analytical Hierarchy Process (AHP) - Dinda Fadila; David JM. Sembiring; Raheliya Br. Ginting; Meiliyani Br. Ginting; Safarul Ilham (JISTI: Jurnal Ilmu Komputer, Sistem Informasi dan Teknologi Informasi, 2025)
Village Fund Allocation in Jati Sari Village is a multi-criteria problem which includes quantitative and qualitative factors. Several criteria that influence the selection of Jati Sari Village in the Village Fund Allocation are quantitative and qualitative. This study aims to develop a Decision Support System (DSS) that utilizes the Analytical Hierarchy Process (AHP) method to determine optimal village fund allocation. The focus of the research will be on Jati Sari Village in Padang Tualang District, Langkat Regency. The research method will use a case study approach to explore the specific context of Jati Sari Village. Through a combination of qualitative analysis, based on the description, discussion and analysis carried out in the previous chapters, it can be concluded that in practice, village fund allocation in Jati Sari Village still uses manual methods which are prone to uncertainty and lack of accuracy.